Peran Adaptive Leadership Presiden Indonesia Dalam Penanganan Covid-19 Rawan Korupsi - Amalia Syauket (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
Abstract The Covid-19 Handling Drama is a national leadership test event. On the other hand, society will depend on its leader and as a leader, he must meet the high expectations of himself. The Covid-19 pandemic is a threat in itself for the Government of Indonesia, if it cannot balance between encouraging economic activity (political interests) and public health (an urgent situation). This article explores the phenomenon of the central role of adaptive leadership in dealing with the Covid-19 pandemic based on constitutional rights taken to save people's lives, but the potential for corruption by using the Normative Juridical approach that prioritizes secondary data. The conclusion that can be drawn from this article is that there is no single best cure for winning this battle because the